Cultural Humility and Mental Health Care in Canadian Muslim Communities - Jisrawi, Athir N.; Arnold, Carrie (Canadian Journal of Counselling and Psychotherapy, 2018)
Canadian Muslims are a growing, oft-scrutinized group that faces critical challenges in a global environment of rising xenophobia and nationalism. Cultural humility is an emerging socially conscious mental health care framework that combines multicultural competencies with personal and institutional accountability in provision of care. Its goal is to strengthen communities by helping individuals in a therapeutic setting and to promote positive institutional change. This article explores the hallmark characteristics of cultural humility as they apply to mental health care for diverse Canadian Muslim communities in the context of identity and belonging, acculturative stresses, and cultural and religious values.